La harina de banano verde con cáscara como sustituto del maíz y la adición de extracto de alcachofa cynara scolymus en la alimentación de pollos - Icaza Bustamante, Laura Carolina (2011)
This investigation was carried out at the premises of the Experimental Farm “Santa Ines belonging to the Technical University of Machala, located on the road to Pasaje Km 5 1 / 2, belonging to the province of El Oro. The objectives of this research were to determine what percentage of optimal inclusion of banana flour in diets of chicks and the effect of the addition of artichoke extract on performance of chickens, measuring food consumption variables, weight gain and feed conversion of chickens from 1 - 49 days of age and finally perform the economic valuation of each of the treatments. With a duration of 6 weeks, 150 broilers used 1 day old. The chickens fed diets with 0, 5, 10, 15, and 20 percent of banana flour in place of corn. The design used was randomized blocks with 5 treatments and 3 replications.10 chicks were distributed in each of the 15 small sheds whose measures were 1 x 1.5 m each. The results came to the following conclusions: de treatments administered with banana flour the Group best weight obtained was the witness followed group with 10%. Lower food consumption was the birds of the treatment group to 5% of banana flour. The highest food conversion obtained in groups with treatment to 20 and 10% of banana flour followed by 5% and 15%. Treatment which gave us more useful was the witness ($50,17), followed by treatment at the 15($49,80) and 10% ($49,72). With the addition of banana meal not presented in any treatment changes in quality and taste of the meat. We obtained a good feed conversion in the groups taking banana flour.